METHODOLOGY AND RESULTS OF MOBILE OBJECT PURSUIT PROBLEM SOLUTION WITH TWO-STAGE DYNAMIC SYSTEM - M. A. Kiselev (Научный вестник МГТУ ГА, 2017)
The experience of developing unmanned fighting vehicles indicates that the main challenge in this field reduces itself to creating the systems which can replace the pilot both as a sensor and as the operator of the flight. This problem can be partial- ly solved by introducing remote control, but there are certain flight segments where it can only be executed under fully inde- pendent control and data support due to various reasons, such as tight time, short duration, lack of robust communication, etc. Such stages also include close-range air combat maneuvering (CRACM) - a key flight segment as far as the fighter's purpose is concerned, which also places the highest demands on the fighter's design. Until recently the creation of an unmanned fighter airplane has been a fundamentally impossible task due to the absence of sensors able to provide the necessary data support to control the fighter during CRACM. However, the development prospects of aircraft hardware (passive type flush antennae, op- tico-locating panoramic view stations) are indicative of producing possible solutions to this problem in the nearest future. There- fore, presently the only fundamental impediment on the way to developing an unmanned fighting aircraft is the problem of cre- ating algorithms for automatic trajectory control during CRACM. This paper presents the strategy of automatic trajectory con- trol synthesis by a two-stage dynamic system aiming to reach the conditions specified with respect to an object in pursuit. It contains certain results of control algorithm parameters impact assessment in regards to the pursuit mission effectiveness. Based on the obtained results a deduction is drawn pertaining to the efficiency of the offered method and its possible utilization in au- tomated control of an unmanned fighting aerial vehicle as well as organizing group interaction during CRACM.